2009
DOI: 10.1080/13682820802546951
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of stuttering frequency during and after speech initiation in unaltered feedback, altered auditory feedback and choral speech conditions

Abstract: Altered auditory feedback effectively inhibits stuttering immediately after speech has been initiated. However, unlike a true choral signal, which is exogenously initiated and offers the most complete fluency enhancement, AAF requires speech to be initiated by the user and 'fed back' before it can directly inhibit stuttering. It is suggested that AAF can be a viable clinical option for those who stutter and should often be used in combination with therapeutic techniques, particularly those that aid speech init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(41 reference statements)
0
17
0
4
Order By: Relevance
“…This interval was chosen based on findings that the likelihood of stuttering increasing with waiting time, when waiting times between 2 and 10 s were examined. In the choral conditions, the voice of the second speaker was presented 0.5 s after the commencement of the visual cue and participants were asked to 'join in', reading along with choral signal immediately after it began (Saltuklaroglu et al, 2008). Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interval was chosen based on findings that the likelihood of stuttering increasing with waiting time, when waiting times between 2 and 10 s were examined. In the choral conditions, the voice of the second speaker was presented 0.5 s after the commencement of the visual cue and participants were asked to 'join in', reading along with choral signal immediately after it began (Saltuklaroglu et al, 2008). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For each participant, it was ensured that no token in the Neutral conditions began with a word that was identified as having a feared sound in the initial position. Considering that stuttering most frequently occurs in word-initial position on the first word of an utterance (Saltuklaroglu et al, 2008), this was deemed the most important distinction between 'feared' and 'neutral' utterances. However, because the stimuli tokens were constructed before conducting the experiment and tokens for each participant were randomly selected from the respective 'feared' and 'neutral' pools after their feared sounds were identified, it was not possible to ensure a priori that a participant's feared sounds did not appear in any word-initial position (i.e., after the first word) in the neutral tokens.…”
Section: Stimulimentioning
confidence: 99%
“…Over time, those who stutter often develop a salient fear of speaking that becomes a deep-rooted obstacle impeding a person's social and vocational opportunities. 1 Treatments for stuttering (which is more often known as stammering in the UK) have been available for children and adults since the 1950s. These treatments have encompassed diverse techniques from the use of carbon dioxide, or pharmacological interventions, to those that are behaviourally based.…”
Section: Chapter 1 Introduction Smentioning
confidence: 99%
“…Both of these approaches have been criticised as offering limited effectiveness owing to the propensity for relapse among people who have completed programmes. 1 In addition to these programmes, the use of mechanical delayed auditory feedback (DAF) devices has been reported to have some success in reducing stuttering. However, there are concerns that these positive outcomes may occur predominantly when reading aloud, rather than in normal conversational interactions.…”
Section: Chapter 1 Introduction Smentioning
confidence: 99%
“…Several authors have reported that choral (or unison) speech brings in immediate and dramatic reduction of dysfluencies in DS (e.gs., Andrews et al, 1983;Freeman & Armson, 1998;Saltuklaroglu, Kalinowski, Robbins, Crawcour, & Bowers, 2009). Recently, Balasubramanian et al (2010) investigated the choral reading effect in two subjects with ANS.…”
Section: Choral Speechmentioning
confidence: 99%